Numerical modelling for analysing drainage in irregular profile pipes using OpenFOAM (2022)
Different methods of two-dimensional and three-dimensional numerical resolution models have been used to predict the air–water interaction in pipe systems in the early twenty-first century, where reliable and adequate results have been obtained when compared with experimental results. However, the study of the drainage process in pressurized systems with air admitted through openings has not been studied using this type of model due to the complexity that this represents. In this research, a two-dimensional numerical model is developed in the open-source software OpenFOAM; this model represents the drainage of an irregular pipe with air admitted by an air valve, defined by a structured mesh. A validation of the numerical model related to the air admitted by the variation of the air valve diameter is also performed. © 2022 Informa UK Limited, trading as Taylor & Francis Group.